Web-based nutrition: a useful resource for cancer patients? - Lazar, Diana Elena; Postolica, Roxana; Hanganu, Bianca; Mocanu, Veronica; Ioan, Beatrice Gabriela (Frontiers in Nutrition, 2023)
One accessible and affordable way to deliver behavior change programs to a large proportion of the growing cancer patients and survivorship community is through web-based methods of nutritional counselling. Objective: The aim of this systematic review was to evaluate the effectiveness of web-based nutritional therapies targeting physical activity, diet, and/or weight control for cancer patients or survivors, primarily disseminated via modern technologies (mobile phone applications) or online. Materials and Methods: A structured search of the PubMed database was conducted. Studies that have focused on physical activity (PA) and dietary change and/or weight control in adolescent and adult cancer patients and survivors have reported outcomes conducted via a broad modality. Results: 9 articles focused on web-based nutrition for patients with cancer and survivors. They were conducted in the United States, Australia, Korea, China, and the United Kingdom, and were published between 2018 and 2022 in a variety of scientific journals. The number of participants ranged from 20 to 159. Conclusion: Web-based nutrition counselling helps cancer patients and survivors improve their dietary intake, impacts their weight and quality of life, and promotes a healthy lifestyle. Future research should evaluate (1) the differences in cost and coverage between face-to-face and web-based nutrition, (2) long-term outcomes, (3) cost-effectiveness, and (4) last but not least, the effectiveness of web-based nutrition in adolescents and children who are cancer patients or survivors, as nutritional status and body composition have a marked impact on clinical outcomes during and after treatment. The strength of this review lies in the large number of randomized controlled trials, which offer a guarantee of effectiveness and objectivity compared to cross-sectional studies.